Ethics in artificial intelligence : analysis of image generator models - Gutierrez Sanchez, Frank Jhosep (2024)
This article on the ethics of artificial intelligence, based on image generation, contains a comprehensive analysis of the ethical and practical dilemmas associated with AI. In the introduction, we highlight the widespread impact of AI on human society and emphasize the importance of addressing the ethical dilemmas arising from its use, distinguishing in areas such as decision making in autonomous vehicles. The methodology proposed includes literature review, ethical self-assessment using specialized tools, and case study analysis to identify ethical and unethical patterns.  The results achieved reveal that the models are capable of generating high quality images in an ethical manner, avoiding the promotion of harmful stereotypes. However, the presence of biases and lack of transparency in the model is determined. Practical ethical considerations for the use of the model in real applications are discussed, highlighting the utmost importance of addressing these challenges in order to ensure a good ethical development and application in the field of artificial intelligence image generation.